Zapomniany polski biblista ks. Franciszek Ksawery Pawłowski (1807–1876) - Nowicki, Tomasz; Zych, Sławomir (The Biblical Annals, 2024)
The article profiles Fr Franciszek Pawłowski, a 19th-century Roman Catholic priest of the Przemyśl diocese, prelate of the local cathedral chapter and professor and rector of the major seminary in Przemyśl. This remarkable figure been noted in, among others, The Polish Biographical Dictionary and The Catholic Encyclopedia, mostly known to specialists but less familiar to the wider circle of researchers and scholars. This article not only presents Fr Pawłowski’s basic biographical data, and the ecclesiastical and academic roles he held, but also his main research interests and his many publications in theology, biblical studies and church history. Particular attention is paid to Pawłowski’s most important work, the four-volume Psalter with a commentary on the Psalms and Lamentations of the prophet Jeremiah, which was published a few years before its author’s death and constitutes his opus vitae. It was dedicated by Fr Pawłowski himself to those interested in Scripture, especially priests and seminarians preparing for the priesthood. Although the basis for his analysis of the biblical text was the Vulgate, and its late 16th-century Polish translation by Fr Jakub Wujek, the author applied modern textual criticism, including comparisons with the Greek and Hebrew texts. Fr Pawłowski’s commentary on the Psalms was highly praised from the outset, as a work testifying to the author’s immense erudition and great diligence. Notably, Fr Pawłowski was also a historian, particularly of the Church of the diocese of Przemyśl, with published sketches on the history of its parishes and monasteries and the schematism of the folk schools and their teachers. Of particular importance was his study on the history, composition and endowment of the Cathedral Chapter in Przemyśl, edited in 1853, and his work Premislia sacra [Holy Przemyśl, or the list and activities of the Roman Catholic bishops of Przemyśl], published in 1869. For such achievements, he was appointed in 1872 as an active member of the Historical-Philosophical Faculty of the newly established Polish Academy of Arts and Sciences in Kraków. Among his legacy are yet other works in the field of biblical studies, which remain to this day as manuscripts in the library of the Przemyśl Chapter, still waiting to be edited and published.